Hands-Off and Hands-On Casting Consistency of Amputee below Knee Sockets Using Magnetic Resonance Imaging. (19th November 2013) - Safari, Mohammad Reza; Rowe, Philip; McFadyen, Angus; Buis, Arjan
Abstract : Residual limb shape capturing (Casting) consistency has a great influence on the quality of socket fit. Magnetic Resonance Imaging was used to establish a reliable reference grid for intercast and intracast shape and volume consistency of two common casting methods, Hands-off and Hands-on. Residual limbs were cast for twelve people with a unilateral below knee amputation and scanned twice for each casting concept. Subsequently, all four volume images of each amputee were semiautomatically segmented and registered to a common coordinate system using the tibia and then the shape and volume differences were calculated. The results show that both casting methods have intra cast volume consistency and there is no significant volume difference between the two methods. Inter- and intracast mean volume differences were not clinically significant based on the volume of one sock criteria. Neither the Hands-off nor the Hands-on method resulted in a consistent residual limb shape as the coefficient of variation of shape differences was high. The resultant shape of the residual limb in the Hands-off casting was variable but the differences were not clinically significant. For the Hands-on casting, shape differences were equal to the maximum acceptable limit for a poor socket fit.